On the curved skate technique of speed skating - van der Eb, J.; Yeadon, M. R. F. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
The classical model of speed skating assumes that the skate travels in a straight line at a constant forward velocity while the sideward push-offs generate motion of the skater's centre of mass (CoM) perpendicular to the skate. However, experimental data suggest that the CoM also gains forward velocity during each stroke. This study explores the impact of the skate's curved trajectory on a skater's velocity. We hypothesized that as a skater leans inward while the skate follows a curved path, the CoM gains forward velocity. To test this, we developed a simplified model using an inverted, extendable pendulum, where the CoM maintains constant height while the leg extends and tilts inward. When the skate is constrained to a circular arc, the model shows an increase in forward CoM velocity during a stroke, a result not observed under the straight-line assumption. This refined model offers a more accurate representation of the mechanics of speed skating strokes.